Conversão de uso e potencial de estoque do carbono nos diferentes usos do solo e cobertura vegetal na bacia do Ribeirãoo Bom Jardim no Triângulo Mineiro (MG) - Resende, Thalita Mendes (2011)
The environments of the Cerrado (Brazilian savannah) are being modified by the conversion use and management of the land. The occupation of the Brazilian Cerrado began in the 1930s and became a priority area for expansion of farming frontier and farming business from the 1970s with the beginning of the period known for the modernization of Brazilian agriculture. Large areas of native vegetation have been and are still being cleared to make room for monocultures of grains (soybeans and corn, mostly), cotton, managed and degraded pasturage areas, deployment of homogeneous forests for coal production and cellulose and, in recent years, the expansion of sugar cane. The annual conversion rate of land use between 1999 and 2005 was 1.55% (Jepson, 2005) and, among the many environmental changes related to deforestation of Cerrado, the erosion, the imbalances in carbon stocks and in nature of carbon sources, and the reducing of the carbon connected to biomass stand out. The middle-region of Triangulo Mineiro / Alto Paraíba, originally covered by Cerrado vegetation, has been heavily cleared and replaced by farming systems for being a pioneer area for expansion of farming business in the Cerrado biome. Thus, this study is to analyze the content and origin of soil organic carbon in the Basin of Ribeirao Bom Jardim (Triangulo Mineiro / MG), after converting the Cerrado vegetation in areas of soybean growing, rotating with corn, and in areas of managed and degraded pasturage, aiming to show the soil degradation potential in comparison to the activities, the management and its time of use. Results of the analysis of total carbon (C%) and carbon isotope (δ13C ) representing four categories of use remaining of Cerrado tree area, rotating soybean and corn growing under no-tillage system, managed pasturage areas and degraded pasturage areas - showed that the use conversion led to important changes in the nature and content of soil carbon, and the furthest enrichment of the carbon tax was in no-tillage system and the furthest impoverishment was found degraded pasturage areas. Although the shown results can not be regarded as representative of the vast area of the Brazilian savannas, they can be used as indicators of significant environmental impacts when natural ecosystems are converted into farming systems.